2019
DOI: 10.1371/journal.pbio.3000525
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase USP6 affects memory and synaptic plasticity through modulating NMDA receptor stability

Abstract: Ubiquitin-specific protease (USP) 6 is a hominoid deubiquitinating enzyme previously implicated in intellectual disability and autism spectrum disorder. Although these findings link USP6 to higher brain function, potential roles for USP6 in cognition have not been investigated. Here, we report that USP6 is highly expressed in induced human neurons and that neuron-specific expression of USP6 enhances learning and memory in a transgenic mouse model. Similarly, USP6 expression regulates N-methyl-D-aspartate-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…Immunoblot analysis was performed as previously described ( 44 ). Antibodies were used as follows: anti-USP25 (Abcam, Cambridge, MA, USA; ab187156, 1:1000), anti-APP (Millipore, Billerica, MA, USA; MAB348, 1:1000), anti-Iba1 (Wako Pure Chemical, Osaka, Japan; 016-20001, 1:500), anti-GFAP (glial fibrillary acidic protein) (Cell Signaling Technology, Danvers, MA, USA; 3670, 1:1000), anti–β-III-tubulin (Abcam, ab18207, 1:1000), anti-HA (hemagglutinin) (Sigma-Aldrich, St. Louis, MO, USA; H6908, 1:1000), anti-ubiquitin (Santa Cruz Biotechnology, Santa Cruz, CA, USA; sc-8017, 1:500), anti–β-actin (Xmbcss, Xiamen, China; bc001, 1:2000), and horseradish peroxidase (HRP)–conjugated secondary antibodies (Thermo Fisher Scientific, 31430 or 31460; 1:3000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblot analysis was performed as previously described ( 44 ). Antibodies were used as follows: anti-USP25 (Abcam, Cambridge, MA, USA; ab187156, 1:1000), anti-APP (Millipore, Billerica, MA, USA; MAB348, 1:1000), anti-Iba1 (Wako Pure Chemical, Osaka, Japan; 016-20001, 1:500), anti-GFAP (glial fibrillary acidic protein) (Cell Signaling Technology, Danvers, MA, USA; 3670, 1:1000), anti–β-III-tubulin (Abcam, ab18207, 1:1000), anti-HA (hemagglutinin) (Sigma-Aldrich, St. Louis, MO, USA; H6908, 1:1000), anti-ubiquitin (Santa Cruz Biotechnology, Santa Cruz, CA, USA; sc-8017, 1:500), anti–β-actin (Xmbcss, Xiamen, China; bc001, 1:2000), and horseradish peroxidase (HRP)–conjugated secondary antibodies (Thermo Fisher Scientific, 31430 or 31460; 1:3000).…”
Section: Methodsmentioning
confidence: 99%
“…Perfusion and brain slice preparation were performed as previously described ( 44 ). Brain slices were stained using the following primary antibodies: anti-Iba1 (Wako Pure Chemical, 019-19741; 1:500), anti-CD68 (Bio-Rad, Hercules, CA, USA; MCA1957, 1:100), anti-PSD95 (Millipore, MAB1596; 1:100), and 6E10 (BioLegend, San Diego, CA, USA; 803001, 1:400).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, FBXO2 ubiquitinates newly synthetized GluN1 and GluN2A subunits in the endoplasmic reticulum (ER) and mediates its degradation via the ER-associated degradation (ERAD) machinery, a mechanism that avoids the formation of supranumerary synapses in the dendritic shaft and aberrant NMDAR-mediated currents (Kato et al, 2005;Nelson et al, 2006;Gascón et al, 2007;Atkin et al, 2015). Synaptic abundance and clustering of GluN1-containing NMDARs are also modulated by the hominoid-specific DUB USP6 (Zeng et al, 2019). By generating a humanized knock-in (KI) mouse expressing USP6 under the control of Ca 21 / calmodulin-dependent kinase II (CamkII) promoter, the authors found that USP6 stabilizes NMDARs at synapses and enhances synaptic function resulting in improved mouse cognitive abilities.…”
Section: Postsynaptic Ubiquitinationmentioning
confidence: 99%
“…Electrophysiology was performed as previously described (Zeng et al, 2019). The 400-µm mouse brain slices were prepared using a Leica VT1200S vibrating microtome in ice-cold dissection solution (64 mM NaCl, 2.5 mM KCl, 1.25 mM NaH 2 PO 4 , 10 mM MgSO 4 , 0.5 mM CaCl 2 , 26 mM NaHCO 3 , 10 mM D-glucose, 120 mM sucrose, pH 7.4, 290-320 mOsm).…”
Section: Electrophysiologymentioning
confidence: 99%